2017
DOI: 10.1038/s41467-017-02365-8
|View full text |Cite|
|
Sign up to set email alerts
|

Midbrain circuit regulation of individual alcohol drinking behaviors in mice

Abstract: Alcohol-use disorder (AUD) is the most prevalent substance-use disorder worldwide. There is substantial individual variability in alcohol drinking behaviors in the population, the neural circuit mechanisms of which remain elusive. Utilizing in vivo electrophysiological techniques, we find that low alcohol drinking (LAD) mice have dramatically higher ventral tegmental area (VTA) dopamine neuron firing and burst activity. Unexpectedly, VTA dopamine neuron activity in high alcohol drinking (HAD) mice does not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 50 publications
4
56
0
2
Order By: Relevance
“…Bursts were defined as the occurrence of two spikes at interspike interval <80 milliseconds and terminated when the interspike interval exceeded 160 milliseconds. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Bursts were defined as the occurrence of two spikes at interspike interval <80 milliseconds and terminated when the interspike interval exceeded 160 milliseconds. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Our initial hypothesis focused on the reciprocal connections among regions of the extended amygdala and the VTA given that optogenetic and chemogenetic studies showed activation or inhibition of some of these neural pathways altered ethanol consumption [ 19 , 36 , 37 ]. We found that accumbal MSNs projecting to the VTA showed differential synaptic plasticity in HDID-1 and control mice after dependence and withdrawal from ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Circuit‐probing techniques highlight the different contribution of VTA DA projections in the reinforcing properties of ethanol (Fig. ; Juarez et al., ). Interestingly, medial VTA DA neurons seem more responsive to ethanol (Fig.…”
Section: Reinforcing Properties Of Ethanol and Subsequent Neural Altementioning
confidence: 99%
“…Longer periods of alcohol exposure may induce homeostatic neuroadaptations not seen at short time intervals, but also the VTA DA neuron subpopulations investigated. Using a 10% ethanol 2BC paradigm of unlimited alcohol access, one group found that VTA‐NAc DA neurons had significantly increased I h current in low alcohol drinking mice and a significantly decreased I h current in high alcohol drinking mice when compared to controls (Juarez et al., ). In contrast, in vitro recordings made from VTA DA neurons 1–6 days after cessation of chronic ethanol consumption in mice (liquid diet, ~23 days) revealed decreases in baseline firing (Bailey et al., ).…”
Section: Reinforcing Properties Of Ethanol and Subsequent Neural Altementioning
confidence: 99%
See 1 more Smart Citation